Implementation of Research and Community Service Information System (SIMLITABMAS) at LPPM Politeknik Piksi Ganesha Based on Laravel Framework - Reyhan Asissrazi Sabian; Candra Mecca Sufyana; Ratnanto Aditiarno (SYSTEMIC RESEARCH: Systemic and Information Technology Journal, 2026)
The management of data and information related to research and community service (LITABMAS) at LPPM Politeknik Piksi Ganesha frequently faces obstacles due to manual processes and difficulties in tracking project progress. This research adopts a case study approach to describe the implementation of the Research and Community Service Information System (SIMLITABMAS) based on the Laravel Framework. The primary objective is to present an efficient, centralized solution. The development of SIMLITABMAS utilizes the Rapid Application Development (RAD) methodology, which emphasizes iterative development and responsiveness to user feedback. The Laravel Framework was selected for its structured Model-View-Controller (MVC) architecture, reliable security features, and rich package ecosystem. The implementation of SIMLITABMAS successfully created an integrated platform to manage various stages of LITABMAS activities, ranging from proposal submission to result reporting. It is expected that this system can improve the effectiveness, efficiency, and transparency in the management of research and community service at LPPM Politeknik Piksi Ganesha.